Risiko Produksi Usahatani Padi Sawah Varietas Unggul di Kecamatan Sandai Kabupaten Ketapang - Yohana, Yohana; Fitrianti, Wanti; Suharyani, Anita (Universitas Galuh, 2025)
Among the sub-districts in Ketapang Regency, Sandai District has the largest output of rice cultivation, which is attributed to the huge number of farmers and the area of land dedicated to rice cultivation. However, as a district with high rice production, farmers in Sandai District also face production risks. This risk is a determining factor in the availability of their crops. This study aims to analyse production risk and the influence of production factors on rice farming risk. This research uses qualitative and quantitative methods, and uses primary and secondary data. This research is a sample study. To determine the influence of production factors on production risk, data analysis was conducted with the coefficient of variation (CV) and the production variance function method to multiple linear regression analysis by Just and Pope. The findings indicated that the production risk associated with rice cultivation had a coefficient of variation (CV) of 33.36% in Sandai Sub-district and the production risk factors that significantly influenced the production of rice farming were NPK fertiliser, pesticides and seeds.